Câmbio e inflação no Mercosul - Caetano, Sidney M.; Fontes, Rosa; Arbex, Marcelo A. (Economia Aplicada, 2003)
This article empirically analyses the Purchasing Power Parity s condition in Mercosur. More specifically, it verifies ifthere is a long run equilibrium between the exchange rate and the internal and external price indexes difference using the cointegration analysis method developed by Johansen. Based on monthly data mostly related to the 90's, the results do not confirm the PPP theory in its absolute and relative versions. Although, they suggest that eventual misalignments in currencies real parity were followed by some nominal exchange rate corrective policy, without interfering too much in the countries natural competitiveness.